Regulating NETosis: Increasing pH Promotes NADPH Oxidase-Dependent NETosis - Khan, Meraj A.; Philip, Lijy M.; Cheung, Guillaume; Vadakepeedika, Shawn; Grasemann, Hartmut; Sweezey, Neil; Palaniyar, Nades (Frontiers in Medicine, 2018)
Neutrophils migrating from the blood (pH 7.35-7.45) into surrounding tissues encounter changes in extracellular pH conditions. Upon activation of NADPH oxidase 2 (Nox), neutrophils generate large amounts of H+ ions reducing the intracellular pH. Nevertheless, how extracelluar pH regulates neutrophil extracellular trap (NET) formation (NETosis) is not clearly established. We hypothesized that increasing pH increases Nox-mediated production of reactive oxygen species (ROS) and neutrophil protease activity, stimulating NETosis. Here we found that raising extracellular pH (range from 6.6 to 7.8; every 0.2 units) increased intracellular pH of both activated and resting neutrophils within 10-20 min (SNARF dual fluorescence measurements). Since Nox activity generates H+ ions, intracellular pH is lower in neutrophils that are activated compared to resting. We also found that higher pH stimulated Nox-dependent ROS production (R123 generation; Flow cytometry, plate reader assay, Imaging) during spontaneous and phorbol myristate acetate (PMA)-induced NETosis (Sytox Green assays, immunoconfocal microscopy, quantifying NETs). In neutrophils that are activated and not resting, higher pH stimulated histone H4 cleavage (Western blots) and NETosis. Raising pH increased Escherichia coli lipopolysaccharide (LPS)-, Pseudomonas aeruginosa (Gram-negative)- and Staphylococcus aureus (Gram-positive)-induced NETosis. Thus, higher extracellular pH promoted Nox-dependent ROS production, protease activity and NETosis; lower pH has the opposite effect. These studies provided mechanistic steps of extracellular pH-mediated regulation of Nox-dependent NETosis. Raising pH either by sodium bicarbonate, or Tris base (clinically known as Tris hydroxymethyl aminomethane, tromethamine or THAM) corrects NETosis. Each Tris molecule can bind 3 H+ ions whereas each bicarbonate HCO3- ion binds 1 H+ ion. Therefore, the amount of Tris solution required to adjust the same level of pH is lower than that of equimolar bicarbonate solution. For that reason, regulating NETosis by pH with specific buffers such as THAM could be effective in managing NET-related diseases.